2011
DOI: 10.3747/co.v18i6.810
|View full text |Cite
|
Sign up to set email alerts
|

The Cost–Utility of Adjuvant Chemotherapy Using Docetaxel and Cyclophosphamide Compared with Doxorubicin and Cyclophosphamide in Breast Cancer

Abstract: ConclusionsRelative to ac, tc is a cost-effective adjuvant chemotherapy regimen, with a cost-effectiveness ratio well below commonly applied thresholds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…They showed that the high cost of the PG regimen was due to the costs of chemotherapy drugs in PG regimen and the Gemcitabin on the eighth day (Chen et al, 2002). Bernard et al in 2011, Younis et al in 2011 and Liubao in separate studies showed that the low cost of the AC regimen was due to the costs of chemotherapy drugs in AC regimen (Liubao et al, 2009;Bernard et al, 2011;Younis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the high cost of the PG regimen was due to the costs of chemotherapy drugs in PG regimen and the Gemcitabin on the eighth day (Chen et al, 2002). Bernard et al in 2011, Younis et al in 2011 and Liubao in separate studies showed that the low cost of the AC regimen was due to the costs of chemotherapy drugs in AC regimen (Liubao et al, 2009;Bernard et al, 2011;Younis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Standard chemotherapy regimens for advanced breast cancer patients is drug regimen containing doxorubicin group which, according to several studies, leads to a reduction in tumor recurrence and increased prognosis of patients . Newly taxane drugs as neoadjuvant regimens is used hoping to get a better response and in neoadjuvant conditions they have shown a good activity and acceptable toxicity and lead to increased pathological complete response (Younis et al, 2011;Mohammadianpanah et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The upfront costs of chemo were derived from local unit costs at the Queen Elizabeth II Health Sciences Centre, in Halifax, Nova Scotia, Canada [30], while the downstream costs of follow up, treatment of recurrent disease and adverse events were derived from the literature (Table 2) [30,31,40,45,47,48]. The analysis took a third-party direct payer perspective.…”
Section: Costs and Utilitiesmentioning
confidence: 99%
“…The long-term phase of the model was based on a previously published model [13,14] and began with all patients in a disease-free state following adjuvant therapy. Patients could experience a local or distant recurrence or die as a result of statespecific or background mortality.…”
Section: Methodsmentioning
confidence: 99%
“…The costs of treating cancer recurrences were derived from a Canadian model of cancer costs [19]. As in our previous work, other health state costs, including adverse events, were derived from the literature [14,20]. All costs were converted into monthly or one-time event-driven costs and adjusted to 2014 Canadian dollars using the Statistics Canada Consumer Price Index health component [21].…”
Section: Costs and Utilitiesmentioning
confidence: 99%